Causes and means of Employee Evading Punishment and ways to Confrontation its consequences - Saleh, Juma Qader (Journal of Legal and Political Studies, 2024)
The topic of employees' impunity is one of the new topics parallel to the development of technology and the communications revolution and the failure of national legislation to issue or amend strict laws to combat administrative and financial corruption, and the exploitation of public office to achieve personal goals under the pretext of the public interest. The creation of impunity does not exist in the legal system of human rights culture as a mechanism to prosecute violators of individual and collective political, civil, economic and administrative human rights. This research paper has addressed this relatively new term by defining it, the reasons and means of its application, its social, administrative and institutional effects, and how to combat it. And achieving justice at the national and global levels. Keywords: Impunity: job violations, collusion and favoritism, criminal and administrative accountability, moral, ethical and political weakness.
Keywords: job violations; collusion and favoritism; criminal and administrative accountability; moral; ethical and political weakness